Fresno Municipal Court Judge Annette LaRue Swearing-in Sandra Snyder as Judge - Watkins, Howard::::::::: (1989)
In ceremony held in Fresno County Plaza Ballroom, both with raised hands and looking at each other as Judge LaRue holds copy of oath